2009
DOI: 10.1002/ijc.24254
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers predict outcome in squamous cell carcinoma of the head and neck after concomitant cisplatin‐based chemoradiation

Abstract: Not all patients with squamous cell carcinomas of the head and neck (HNSCC) benefit from concurrent cisplatin-based chemoradiation, but reliable predictive markers for outcome after chemoradiation are scarce. We have investigated potential prognostic biomarkers for outcome in a large group of patients. Ninety-one tumor biopsies taken from consecutive HNSCC patients were evaluated for protein expression on a tissue microarray. Using immunohistochemistry, 18 biomarkers, involved in various cellular pathways were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
31
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 79 publications
4
31
1
Order By: Relevance
“…In fact, the synergistic/additive effect of cisplatin plus other drugs has been demonstrated in nasopharyngeal cancer (NPC) cell lines (NPC-TW01 and NPC-TW04), human HNSCC cell line SCC25, and human epidermoid carcinoma A431 cells 34,35. It has also been shown that a combination of different agents could induce more antitumor efficiency;36 thus, our findings are consistent with those investigations.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, the synergistic/additive effect of cisplatin plus other drugs has been demonstrated in nasopharyngeal cancer (NPC) cell lines (NPC-TW01 and NPC-TW04), human HNSCC cell line SCC25, and human epidermoid carcinoma A431 cells 34,35. It has also been shown that a combination of different agents could induce more antitumor efficiency;36 thus, our findings are consistent with those investigations.…”
Section: Discussionsupporting
confidence: 92%
“…The association between MRP2 expression and the clinical outcome has been demonstrated in various types of tumors (25)(26)(27), but its prognostic role in CRC remains to be clarified. Further study is required to elucidate the role of MRP2 expression in poor response patients who received platinum-based therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Last but not least, another advantage of TMA is cost and time savings. TMAs have been used to validate immunohistochemical expression profiles of proteins that have been indicated as predictors for laryngeal carcinoma [52, 53]. Using AQUA protein analysis on TMAs composed of annotated HNSCC cohorts, Psyrri et al have identified several prognostic biomarkers as well as biomarkers that distinguish HPV-positive versus HPV-negative HNSCCs [34, 5457].…”
Section: Research Areas Of the Hncg Translational Research Subcommitteementioning
confidence: 99%
“…In recent years, the data imply a genetic basis for a susceptibility to the development of radiation injury after (chemo)radiotherapy [52, 53, 58]. A recent study [59] examined whether patients with severe radiation-induced sequelae (RIS) both show a low capacity of radiation-induced CD8 lymphocyte apoptosis (RILA) in vitro and bear certain SNPs located in candidate genes associated with the response of cells to radiation.…”
Section: Research Areas Of the Hncg Translational Research Subcommitteementioning
confidence: 99%